Case report: If it is not asthma—think of lymphangioleiomyomatosis in younger female patients - Kirkeby, Malene Helligsø; Bendstrup, Elisabeth; Rose, Hanne Krogh (Frontiers in Medicine, 2024)
Lymphangioleiomyomatosis (LAM) is a rare lung disease predominantly affecting women, and it is characterized by the proliferation of smooth muscle cells and cystic lung destruction. LAM diagnosis is challenging due to varied clinical presentations and resemblance to common conditions like asthma. We present two female cases where LAM was initially misdiagnosed. Case 1 describes a woman treated for asthma-chronic obstruction pulmonary disease overlap syndrome, whilst also undergoing treatment with VEGF inhibitor pazopanib for a retroperitoneal leiomyoma, the latter responding well to treatment. Due to progressive dyspnea, pazopanib induced pneumonitis was suspected. High resolution computed tomography (HRCT) showed changes compatible with LAM. Revision of biopsies showed that the leiomyoma was in fact a lymphangioleiomyoma, and VEGF-D was increased. Both supported the LAM diagnosis. Treatment with mTORC1 inhibitor sirolimus was initiated. Case 2 describes a woman, who in resemblance was also suspected of asthma, and did not respond clinically to treatment. After several years, HRCT was performed and suspicion of LAM was raised. Transbronchial biopsy and later, an increased VEGF-D supported the LAM diagnosis. As in case 1, treatment with sirolimus was initiated. These cases underscore the importance of reevaluating diagnoses when treatments fail to yield expected results. Improved awareness and early detection of LAM can enhance patient outcomes and life quality. Early LAM diagnosis is vital as mTORC1 inhibitors like sirolimus can prevent further decline in lung function. Notably, Case 2's response to pazopanib treatment supports suggestions of its potential as a second-line therapy for perivascular epithelioid cell tumors (PEComas), including LAM.